Pengaruh Profitabilitas, Leverage, dan Likuiditas Terhadap Manajemen Laba Pada Perusahaan Sektor Food and Beverages Di Bei Periode Tahun 2019-2023 - Angela Marenda, Nashya; Safari, M. Dedy Eko Trisyono; Pratiwi, Lavenia Indanus (Mabny: Journal of Sharia Management and Business, 2025)
This study aims to determine and analyse whether Profitability, Leverage, and Liquidity affect earnings management. This type of research is quantitative which is used to examine predetermined populations and samples. In this study, the sampling used purposive sampling technique, namely based on predetermined criteria as many as 20 Food and Beverages companies on the BEI for the 2019-2023 period. The first hypothesis of this study concluded that the profitability variable partially has no effect on earnings management, companies that have high profits do not necessarily produce high earnings management. The second hypothesis in this study is that leverage is concluded to have no effect on earnings management, the results show that the higher the leverage in the company, the more earnings management will decrease if management cannot manage finances so as to cause large debts that have an impact on the company's difficulty paying its obligations. In the third hypothesis, liquidity also has no effect on earnings management, which means that when the value of the liquidity ratio is low, the company has difficulty paying its short-term debt. The results in testing together (simultaneously) show that the variables of profitability, leverage, and liquidity have no effect on earnings management.